STUDI KORELASI ANTARA KONSEP MORAL DENGAN SIKAP BERAGAMA PADA SISWA KELAS VI MI MIFTAHUL HUDA CANDI KEC. TODANAN KAB. BLORA TAHUN AJARAN 2023/2024 - Fitri Purnamasari, Fitri Purnamasari; Teryshia Mustaqimatul Aliyah; Jaenal Abidin; Siti Febiliana Nur Afifah; Ita Mufidah; Imam Fathoni (https://www.ejournal.smaamc.sch.id/index.php/belajar, 2024)
A moral concept is a view or thought about an issue, which in this case is about a person's behavior. Meanwhile, religious attitudes have the meaning of feelings. a person's thoughts and tendencies in carrying out real life procedures and managing relationships with and responsibilities to God, to society and the natural surroundings. , this type of research is a descriptive qualitative approach, with data sources from school principals, teachers and other documents. The results of this research are that there is a correlation between moral concepts and religious attitudes in class VI students at MI Miftahul Huda Candi in the 2023/2024 academic year. The majority of students show high religious attitudes, which may be related to the religious education implemented at school. However, there are still a number of students who show low religious attitudes, which require further attention from the school.